Strategy : Theory and Practice - Clegg, Stewart R (SAGE Publications, Ltd. (UK), 2022)
Written by an expert team and praised for its refreshing approach, this essential text offers a critical, holistic understanding of strategy theory and practice. The fourth edition has been fully updated to include: • Coverage of contemporary issues including the Covid-19 pandemic, climate change and digitalization • Topical and engaging case studies such as Disney’s Strategy and Covid-19, Netflix Versus Amazon: Dynamic Capabilities for Global Success, and PS5, Xbox and BMW: Chips and Supply Chains • A wealth of new examples of strategy in practice from world-renowned organisations such as Google, Uniqlo, Tesla, IKEA, and Airbnb Suitable for both undergraduate and postgraduate study, Strategy: Theory and Practice encourages readers to engage critically with the internal and external factors that shape strategy in the real world. A selection of tried and tested online resources, including a teaching guide, PowerPoints, an online case study bank and test bank of questions have been developed to support lecturers using the book in their teaching.  Stewart Clegg is Professor at the University of Sydney, Emeritus Professor at the University of Technology Sydney, and Visiting Professor at the University of Stavanger, University of Johannesburg, and Nova School of Business and Economics. Christos Pitelis is Head of Department of International Business and Professor of International Business and Sustainable Competitiveness at the University of Leeds, and Life Fellow at Queens’ College, University of Cambridge. Jochen Schweitzer is an Associate Professor at the University of Technology Sydney. Andrea Whittle is Professor of Management at Newcastle University Business School.